Assessing Mindfulness-Based Teaching Competence: Good Practice Guidance - Rebecca Crane PhD; Lynn Koerbel MPH; Sophie Sansom PhD; Alison Yiangou MA (SAGE Publishing, 2020)
Inclusion of assessment of teaching competence in Mindfulness-Based Program (MBP) teacher training enables international benchmarking of standards, which in turn underpins the integrity of this emerging field and the potential to deliver effective, transformative interventions. However, there is a risk that the inclusion of competence assessment could lead to reductionism and undermining of the pedagogical features that make mindfulness-based teaching distinct. It can also make the costs of training prohibitive. The science underpinning the integrity of competence assessment is not yet robust enough to justify wide scale implementation, but when feasible, including the option for assessment enables trainees to engage in rigorous and effective training processes. When assessment is included, it is critically important that the process is held with awareness and sensitivity, and is implemented by experienced assessors with thoughtful governance. Navigating these issues involves balancing rigour with accessibility and pragmatism. This paper lays out some guidelines for good practice for MBP teaching assessment, and raises unresolved dilemmas and questions.